KECERAHAN WARNA IKAN KOI (Cyprinus carpio L.) PADA PEMBERIAN KOMBINASI TEPUNG KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) DAN MANGGIS (Grancinia mangostana L.) - Amalia, Baiq Rizki; Lumbessy, Salnida Yuniarti; Dewi, Rizki Salnida (JURNAL AKUAKULTURA, 2023)
This study aims to analyze the effect of the combined use of dragon fruit peel flour (TKBNM) and mangosteen (TKBM) in feed on the brightness of koi fish color. The research was conducted for 50 days, in the Laboratory of fish production and reproduction at Mataram University using an experimental method with a complete randomized design (CRD) consisting of 4 treatments and 3 replications, namely: A: 100% pellets (control), B: 90% pellets + 5% TKBNM + 5% TKBM, C: 80% pellets + 10% TKBNM + 10% TKBM, and D: 70% pellets + 15% TKBNM + 15% TKBM. Test parameters included carotenoid content, fish color brightness, absolute weight, absolute length, specific growth rate, feed conversion ratio, feed utilization efficiency and survival and water quality. Data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan's test. The results showed that the addition of red dragon fruit peel and mangosteen flour to commercial feed can increase the brightness of koi fish color and can affect specific growth rate and absolute weight. The addition of red dragon fruit peel flour and mangosteen as much as 5% provides the same ability as commercial feed in increasing the specific growth rate and absolute weight of koi fish which is 0.94% / day and 0.42 g which is supported by the carotenoid content of koi fish of 9.67 µmol / g, Redness (a *) value of 8.47 Yellowness (b *) of 8.03, Lghtness (L *) of 56.24 and Hue of 40.